Respostas psicofisiológicas de nadadores brasileiros de acordo com o sexo, especialidade competitiva e performance - Silva, Glauber Castelo Branco (2018)
The aim of this study was to compare cortisol response between the sexes, swimming specialties and performance in young athletes, as well as investigating the relationships between cortisol and anxiety. The sample consisted of 35 swimmers (19 men and 16 women) aged 15.41±0.51 years, assessed during the Brazilian National Juvenile Swimming Championship. The Competitive State Anxiety Inventory (CSAI-2) was used to measure state anxiety and salivary collections were made according to the Elisa protocol (Salivette®/DSL-10-671000 ACTIVE® Cortisol EIA Kit). The women exhibited greater cognitive anxiety (woman=22.28±5.16* vs males=16.84±6.15, p=0.012) and somatic anxiety (woman=19.14±5.43* vs males=15.15±2.40, p=0.008). Sprinters showed higher somatic anxiety than middle and long-distance swimmers (sprinters=18.43±4.80* vs middle and long distance=15.35±3.46, p= 0.042) and low-performance swimmers higher cognitive anxiety than their high-performance counterparts (low performance =21.80±6.42* vs high performance= 17.55±5.07, p=0.049). Sprinters displayed higher pre-competition cortisol levels (sprinters= 0.41±0.12* vs = 0.32±0.13, P= 0.05). Male swimmers showed negative relationships between cognitive anxiety and self-confidence (r= -0.56; p=0.001) and somatic anxiety (r= -0.45; p=0.001), as well as middle and long-distance swimmers (r= -0.52, p=0.001) and high-performance swimmers (r= -0.78, p=0.001). A psychophysiological relationship was observed in low-performance athletes between somatic anxiety and pre competition cortisol. (r= -0.50; p=0.002). Concludes, male, middle-distance and high-performance swimmers are more self-confident and display lower anxiety levels during competition.